A clinical study of large ovarian cyst with various presentations: prospective interventional study - Nalini, Yellapragada Lakshmi; Sharma, Deepak; Chandra, A. Sarath; Deepshika, B. S. Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The definition of huge ovarian cysts is not well described in the literature. Some authors define large ovarian cysts as those that are more than 10 cm in diameter as measured by preoperative scans. An ovarian cyst is a common gynecological problem and is divided into two main categories; physiological and pathological. Aims and objectives of this study was to find out various presentations of large ovarian tumour. Methods: It was a prospective interventional study done for a period of two year from March 2015 to March 2017 in Department of Obstetrics and Gynecology as well as in Department of General Surgery. During the study period a total of 30 study participants were enrolled. Results: Majority of the study participants were in the age group of 18-28 years (66.66%) and 33.33% were in the age group of 28-38 years. Near about 33.33% were uncomplicated. Near about 33.33% presented with tortion, 7% with rupture of cyst, infection was seen in 13.33%. About 13.33% were malignant cyst. Conclusions: Large ovarian cysts are a clinical challenge for Gynaecologists. Quite a good number of these cases can end up with complications and hence, all of them have to be subjected to surgery.